The Role Of The Regional Election Commission (Kpud) For Increasing Voter Participation (Study In Timor Tengah Selatan District, Ntt Province) - Ernawati DAENG; Adriana Rodina FALLO; David Wilfrid RIHI; Andreas PENI (PT Keberlanjutan Strategis Indonesia, 2023)
One indicator of the success of holding elections is increasing voter participation, so the Regional General Election Commission (KPUD) of TTS Regency, as the election management body, must strive to increase voter participation to exercise their right to vote. This research uses qualitative methods and a case study approach and is located in TTS District. Primary data in this study were taken through direct interviews with KPUD members and the community involved and not involved in the 2019 TTS Regency Election with a total of 38 informants, while the secondary data in this study were taken from library data, journals and election documents for 2019 then the collected data were analyzed using data analysis techniques from Yin (2008: 34) which were predominantly carried out in case study research. The results of the study found that the role of the TTS Regency KPUD in increasing community participation was through; (1) Electoral education, namely using; (a) conducting outreach, (b) forming democracy volunteers and (c) establishing election smart houses but the turnout rate of voters in TTS Regency is still low due to factors of no KTP, distance to the residence, wandering, not having a mobile phone, apathy and resignation, being late find out information and the lack of signal coverage in TTS District in several locations